ChemInform Abstract: Hybrid Two‐Dimensional Materials in Rechargeable Battery Applications and Their Microscopic Mechanisms. Issue 38 (September 2016) - Wang, Xi; Weng, Qunhong; Yang, Yijun; Bando, Yoshio; Golberg, Dmitri
Abstract: Review: 305 refs.